Annual risk reporting of listed companies in Malaysia - Atan, Ruhaya; Sutan Maruhun, Enny Nurdin; Wan Abdul Kadir, Wan Hasnah; Jusoff, Kamaruzaman (David Publishing Company, 2010)
This study examines risk reporting in annual reports of Malaysian listed companies. The mandatory and voluntary disclosures of risk information are analyzed and the authors examine whether a relationship exists between company size, leverage, and industry type and risk disclosure levels. 150 listed companies from five industries are selected as sample. Content analysis and risk disclosure index of dichotomous measurement are used in data collection. Overall the results indicate that level of risk information disclosed in the annual reports is still minimal. OLS (Ordinary least squares) regression analysis indicates that the level of risk information disclosure is positively associated with size and not with leverage. However, a mixed result has been found for industry type; where only property industry shows a significant relationship with level of risk disclosure, and not for the other industries. This study contributes to financial reporting literature in relation to risk reporting, particularly the practice of Malaysian companies. Findings from this study are also useful to regulators and accounting standard setting body to assess the level of compliance to regulations and standards relating to risk reporting by these companies. More studies are required to further understand the importance of risk information disclosure, such as risk disclosure within specific industry, cross-country studies and usefulness of risk information disclosure from the stakeholders’ perspectives.